2016
DOI: 10.1186/s13722-016-0056-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep abnormalities associated with alcohol, cannabis, cocaine, and opiate use: a comprehensive review

Abstract: Sleep abnormalities are associated with acute and chronic use of addictive substances. Although sleep complaints associated with use and abstinence from addictive substances are widely recognized, familiarity with the underlying sleep abnormalities is often lacking, despite evidence that these sleep abnormalities may be recalcitrant and impede good outcomes. Substantial research has now characterized the abnormalities associated with acute and chronic use of alcohol, cannabis, cocaine, and opiates. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
193
2
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(221 citation statements)
references
References 218 publications
(444 reference statements)
8
193
2
10
Order By: Relevance
“…This lack of significant relationship between lifestyle factors and insomnia is not in line with previous research in non-musician samples (Angarita et al, 2016;Kredlow, Capozzoli, Hearon, Calkins, & Otto, 2015). Our results suggest that physical activity, use of marijuana, and smoking are unrelated to sleep among musicians.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…This lack of significant relationship between lifestyle factors and insomnia is not in line with previous research in non-musician samples (Angarita et al, 2016;Kredlow, Capozzoli, Hearon, Calkins, & Otto, 2015). Our results suggest that physical activity, use of marijuana, and smoking are unrelated to sleep among musicians.…”
Section: Discussioncontrasting
confidence: 39%
“…A recent review confirms the role of acute and chronic use of alcohol, cocaine, cannabis, and opiates in developing sleep problems (Angarita, Emadi, Hodges, & Morgan, 2016). Bellis et al ( 2007) also pointed to the link between the stressful environment many musicians experience, especially famous pop and rock musicians, where alcohol and drug misuse is abundant and leads to health problems.…”
mentioning
confidence: 99%
“…Perhaps surprisingly, SR sleep times around 1 week of abstinence were remarkably accurate, without substantial under-or overreporting. Although sleep in chronic cocaine users at this point of abstinence does not reflect the deterioration that comes with more sustained abstinence, 17,18,24 the accuracy of the SR-at least in a sleep laboratory environment with strict timein-bed controls-suggests that it could nevertheless be useful for studying sleep in this population when more objective measurement is not feasible. However, a greater frequency of PSG measurement of sleep would be required to ascertain, for example, whether sleep time perception is accurate prior to the first point tested in this study and what the time course is for the misperception that was observed at the second time point.…”
Section: Discussionmentioning
confidence: 99%
“…Like chronic users of other substances including alcohol, opiates, and cannabis, [7][8][9][10][11][12][13][14][15] chronic cocaine users have severely disrupted sleep 16,17 that may persist for weeks, months, or even longer (for review, see Angarita et al 18 ). Over the first several weeks of abstinence, polysomnographically (PSG) measured sleep in chronic cocaine users worsens, with shortening total sleep time, diminishing REM sleep (rapid eye movement sleep; a sleep phase characterized by rapid and random eye movements, muscle inhibition, and brain waves similar to those exhibited during wakefulness) time, increasing sleep latency, and chronically decreased slow-wave sleep time.…”
Section: Introductionmentioning
confidence: 99%
“…22 Despite the perception of short-term relief, these substances retard function by disturbing learning, memory and sleep architecture. 22 For insomnia, first-line management involves cognitive behavioural strategies including sleep or bedtime restriction, avoiding screens before bedtime and other sleep hygiene measures. 44 …”
Section: Psychological Treatmentsmentioning
confidence: 99%